Prevalence of lead toxicity in adolescents in Kuwait - Reem Jallad; Muddanna S. Rao; Abdur Rahman (BMC, 2021)
Abstract Background Elevated blood lead level (EBLL) is a public health problem in both developing and industrialized countries. Being a petrochemical-based economy, lead (Pb) levels are expected to be high in Kuwait, but systematic data on population exposure are lacking. This study aimed at determining the prevalence of EBLL in adolescents in Kuwait. Methods Adolescents (N = 1385; age range 11-16 years) were cross-sectionally selected from public middle schools from all Governorates of Kuwait, utilizing multistage cluster random sampling. Pb in whole blood was analyzed by inductively coupled plasma mass spectrometry. Distribution of blood Pb levels (BLL) among Governorates and sexes were compared by non-parametric tests and the prevalence of EBLL (defined as BLL above the CDC reference level of ≥5 μg/dL) was estimated by χ2 test. Binary logistic regression was used for assessing the association between EBLL and Governorate. Results Median (IQR) BLL was 5.1(3.6-7.1) μg/dL [4.9 (3.8-6.5) μg/dL in males and 5.4 (3.3-7.6) μg/dL in females; p = 0.001]. In the overall sample, 51% had BLL ≥5 μg/dL; 13% had ≥10 μg/dL and 3% > 20 μg/dL. Prevalence of EBLL was 47% in males and 56% in females (p < 0.001). EBLLs were clustered in Al-Asima, Al-Ahmadi (in both sexes); Al-Jahra (in males) and Mubarak Al-Kabeer (in females) Governorates. Conclusions EBLL is a significant public health problem in adolescents in Kuwait. Urgent public health intervention is required in areas with EBLL, and the sources of exposure need to be identified for prevention.